3(x+4)=7x+12-4x

Simple and best practice solution for 3(x+4)=7x+12-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+4)=7x+12-4x equation:



3(x+4)=7x+12-4x
We move all terms to the left:
3(x+4)-(7x+12-4x)=0
We add all the numbers together, and all the variables
3(x+4)-(3x+12)=0
We multiply parentheses
3x-(3x+12)+12=0
We get rid of parentheses
3x-3x-12+12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 9=3-z | | 7d-22=4d | | x2−3x−5=0 | | 12-3t=3 | | 2(4x-3)-7(8x-9)=14 | | 2h^2+4h=31 | | w/7+5=3 | | 2/9c=6 | | 3(x-4)=-6x+11+9x | | 3x+5=2^3 | | x2+11x=12 | | 3.16=3y-2 | | 3n+3(-n)=-6 | | 12x/7+10=7 | | 5/6x+5=7 | | 100x=11+(29/99) | | 100x=11+29/99 | | 3x-2.4x+8=0 | | 6s−4=8(2+41​s) | | 2(x-7)+2(x)=(x+9)+(x-7)+(x+2) | | 500+(11x)=1000+(7x) | | 1/2(12x+10)-4=-1/5(35x-35) | | 7(x=7)+3=-3(x-8)-2 | | 4x3+2=x | | 16^(5-x)=4 | | 100x=11+0.29292929 | | 3+(8-4)x2-12=2 | | 100x=11+0.29 | | 30x-(-x+6)+(-5x+4)=(5x+6)+(-8+3x) | | 7(x+7)+3=-3(x-8)-2 | | H(64)=-16t+64t | | Y=x(x-2)(x-4) |

Equations solver categories